Detection of citrus psorosis virus (CPsV) and citrus tristeza virus (CTV) by direct tissue blot immunoassay - Djelouah K.; D'Onghia A.M. (Improvement of the citrus sector by the setting up of the common conservation strategies for the free exchange of healthy citrus genetic resources, 2001)
Detection of citrus psorosis virus (CPsV) and citrus tristeza virus (CTV) by direct tissue blot immunoassay